Histological organization of thyroid and interrenal glands of the pearl mullet, Alburnus tarichi (Cypriniformes: Cyprinidae) from Lake Van Basin of Turkey - Kaptaner, Burak (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, histological organizations of the thyroid and interrenal glands were first investigated in pearl mullet (Alburnus tarichi Güldenstädt, 1814), living in the Lake Van basin in Turkey. The serial sections taken from the subpharyngeal region and kidney were stained with hematoxylin and eosin, Mallory’s trichrome and periodic acid-Schiff/hematoxylin and then examined. The histological examinations showed that the thyroid gland of pearl mullet was unencapsulated and the thyroid follicles were scattered diffusely in the subpharyngeal region, located at the dorsal and lateral aspects of the ventral aorta. The follicles had colloid-filled lumens and were surrounded by simple follicular epithelial cells varying in shapes (squamose, cuboidal and cylindrical). Thyroid follicles were not found in any areas of the kidney. The interrenal and chromaffin tissue were observed to be associated with postcardinal vein with its branches in the head of the kidney. The interrenal cells having a deeply eosinophilic cytoplasm were determined adjacent to branches in the head kidney. The eosinophobic chromaffin cells were found to show two different distributions. They were observed as being intermingled with the interrenal cells and formed separate groups surrounded by a thin connective tissue in the walls of the major veins. Both interrenal and chromaffin cells displayed a negative periodic acid-Schiff reaction.